Plasma biomarker proteins for detection of human growth hormone administration in athletes - Tan, Sock-Hwee; Lee, Albert; Pascovici, Dana; Care, Natasha; Birzniece, Vita; Ho, Ken; Molloy, Mark P.; Khan, Alamgir (Scientific reports, 2017)
Human growth hormone (GH) is a naturally occurring hormone secreted by the pituitary gland with anabolic and growth-promoting activities. Since an increased availability of recombinant GH (rGH) for the treatment of GH-deficient patients, GH has been abused in sports and it is prohibited. “GH-isoform” and “biomarkers” tests are currently available for detection of GH abuse in sports, however both methods suffer from shortcomings. Here, we report on a proteomic approach to search for novel protein biomarkers associated with rGH administration in non-elite athletes. In this study, participants received either placebo or rGH for 8 weeks, and were followed over a 6-week washout period. We used 2-D DIGE and iTRAQ LC-MS/MS analyses to expose rGH-dependent marker proteins. Eight rGH-dependent plasma proteins namely apolipoproptein-L1, alpha-HS-glycoprotein, vitamin D-binding protein, afamin, insulin-like growth factor-binding protein-3, insulin-like growth factor-binding protein-ALS, lumican and extracellular matrix proteins 1 were identified. Apolipoprotein L1 and alpha-HS-glycoprotein were validated by Western blots to confirm their identities and expression patterns in rGH- and placebo-treated subject cohorts. Independent confirmation of these putative GH-responsive biomarkers would be of value for clinical practices and may have sports anti-doping utility.